Pengelolaan Hotel RedDoorz Syariah Near Sun City Mall Sidoarjo: Tinjauan Fatwa DSN-MUI - Muhammad Faiz (Program Studi Hukum Ekonomi Syariah, 2026)
The increasing demand for halal tourism in Indonesia is not balanced by the consistent implementation of sharia principles in the hospitality sector, including the uneven ownership of halal certificates in several hotels that claim to apply sharia principles. This study aims to analyze the suitability of the management of the RedDoorz Syariah Hotel Near Sun City Mall Sidoarjo with Fatwa of National Sharia Board – Indonesian Ulama Council (DSN-MUI) on Guidelines for the Implementation of Sharia Hotel Business. The method used is qualitative with a case study approach through observation, in-depth interviews, and document analysis. The results of the study show that although hotels do not yet have an official certificate from the MUI, in practice they have implemented most of the sharia principles from the Fatwa of DSN-MUI, such as screening non-mahram guests, providing worship facilities, and preventing immoral acts. However, imperfections were found in the aspect of using Islamic financial services and the absence of a Sharia Supervisory Board (DPS) in its structure. The implication of these findings is the importance of more systematic supervision and refinement of financial aspects to achieve comprehensive sharia compliance as well as evaluation material for the sharia hotel certification process.